If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 1x + 9 Reorder the terms: 4x = 9 + 1x Solving 4x = 9 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4x + -1x = 9 + 1x + -1x Combine like terms: 4x + -1x = 3x 3x = 9 + 1x + -1x Combine like terms: 1x + -1x = 0 3x = 9 + 0 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 75=-5(x+5) | | 16y=-5 | | 4b^2-4b-24=0 | | x^2+3x-8=8x-2 | | 18X+216=18(X+216) | | -4p+5=7 | | 30x^2+10x= | | -8/2=c | | 3y=27-6y | | 40=b-(-45) | | 2(4a-12)+3a=6a-1 | | 2x+-4x=-6 | | 2/15x=18/15 | | 4z=-16 | | 2x-4x=-6 | | 21/2x11/5 | | 14w^2+181w+75= | | 189-99= | | 2/3(6x-9)+1/4(4x-12)=18 | | 3x^2+6=-9x | | 1-1/5=x | | 100(9-4.5)=350 | | 1/5-1=x | | -x+3x=18 | | 17=12+b | | 1/2-1=x | | 5.5n=2.3 | | 2-d=3/4 | | 18z+3x=5y-3x+12 | | 6x-(-4)=10x | | 6x(-4)= | | 6+4-3*1-7= |